Probe of Password Authenticated 3P-EKE Protocols - Raghuvamshi, Archana; Parvataneni, Premchand (International Journal of Computer Sciences and Engineering, 2025)
To establish a secure communication over unreliable networks, Password-Authenticated Encrypted Key Exchange (PA-EKE) protocols plays a pivotal role. Diffie & Hellman (D-H) (1976) proposed a first key agreement protocol, which is suffered from man-in-the-middle attack. To overcome a flaw, many authors proposed password-authenticated key agreement protocols. Chang & Chang (2004) proposed a novel password-authenticated 3P-EKE protocol with round efficiency. In contrast, Yoon & Yoo (2008) notified an undetectable online dictionary attack on this protocol and proposed an improvement over it. Later, Padmavathy et al. cryptanalyzed the Yoon-Yoo’s protocol and proposed PSRJ Protocol. Subsequently, Archana et al. (2012) notified a detectable online dictionary attack on PSRJ Protocol. Afterward, an improvement over the Yoon-Yoo’s protocol is proposed by Raj et al. (2013), which is cryptanalyzed by Archana et al. (2013). In this paper we have analyzed all the above protocols at their performance level.